Global scientific trends on the immunomodulation of mesenchymal stem cells in the 21st century: A bibliometric and visualized analysis - Wang, Zhongqing; Sun, Yuqiang; Shen, Rou; Tang, Xia; Xu, Yingxin; Zhang, Ye; Liu, Yao (Frontiers in Immunology, 2022)
Background: Since the discovery of the immunomodulatory functions of mesenchymal stem cells (MSCs), their application in immunomodulation has attracted considerable attention, and an increasing number of studies have been conducted worldwide. Our research aimed to investigate the global status and trends in this field. Methods: Publications on the immunomodulatory functions of MSCs from 1 January 2000 to 7 March 2022 were retrieved from the Web of Science Core Collection. The data were studied and indexed using the bibliometric methodology. Visualization analysis, co-authorship, co-occurrence analysis, and publication trends in MSC immunomodulation were conducted using the VOSviewer software. Results: In total, 4,227 papers were included in the study. The number of publications and research interests has significantly increased globally. China published the highest number of related articles, while the US published articles with the highest number of citations. Stem Cell Research & Therapy had the highest number of publications. Sun Yat-sen University, Shanghai Jiao Tong University, Harvard University, and Seoul National University were the most contributive institutions. Furthermore, the studies were divided into four research hotspots for MSC immunomodulation: MSC immunomodulation in regenerative medicine, the effects and mechanisms of MSC immunomodulation, MSC therapy for immune diseases, and the cell source of MSCs. Conclusion: This study indicates that the number of publications on MSC immunomodulation will increase in the future, and MSC immunomodulation mechanisms and clinical applications of MSC immunotherapy should be the next hotspots in this research field.